Prognostic Value of Bleeding in Gastrointestinal Stromal Tumors: A Meta-Analysis. (28th July 2021) - Fan, Xin; Han, He; Sun, Zhiyu; Zhang, Liwen; Chen, Gong; Mzee, Said Abdulrahman Salim; Yang, Hanqing; Chen, Jixiang
Background: Gastrointestinal bleeding is the most common clinical manifestation of gastrointestinal stromal tumor. It is of great significance to the prognosis of patients. But the results are controversial. The purpose of this study was to evaluate the relationship between gastrointestinal bleeding and clinical prognosis in patients with GIST. Methods: A systematic literature search was performed in Pumbed, Cochrane Library, EMBASE, ClinicalTrials.gov, CNKI, VIP and wanfang databases with the pattern of unlimited languages. 12 studies with 2781 individuals were included in the final analysis. The overall survival (OS), recurrence-free survival/disease-free survival (RFS/DFS) and related factors affecting bleeding in patients with gastrointestinal stromal tumor (GIST) were extracted. Hazard ratio (HR) and 95% confidence interval (CI) were used for in the meta-analysis. Results: A total of 12 articles were included in the study, including 2781 patients with GIST, including 845 patients with gastrointestinal bleeding. The OS of GIST patients with gastrointestinal bleeding was significantly worse (HR = 2.54, 95% CI = 1.13-5.73, P = 0.025). But there was no significant difference in RFS between gastrointestinal bleeding patients and non-bleeding patients (HR = 1.35, 95% CI = 0.70-2.61, P = 0.371). Further analysis of the related factors of GI bleeding in GIST patients was observed, besides the aging factor (HR = 1.02, 95% CI = 0.69-1.50, P = 0.929), Small intestinal stromal tumor (HR = 0.56, 95% CI = 0.41-0.76, P < 0.001), tumor diameter ≥ 5 cm (HR = 2.09, 95% CI = 1.20-3.63, P = 0.009), Mitotic index ≥ 5/50 HPF (HR = 1.66, 95% CI = 1.11-2.49, P = 0.014) and tumor rupture (HR = 2.04, 95% CI = 1.0-3.82, P = 0.026) all increased the risk of GI bleeding in patients with GIST. Conclusions: The OS of GIST patients with GI bleeding was worse than non-GI bleeding, but had no significant effect on RFS. Nevertheless the aging factor, the location of GIST in the small intestine, tumor diameter ≥ 5 cm, Mitotic index ≥ 5/50 HPF and tumor rupture all increased the risk of GI bleeding in patients with GIST.